Postbiotics for Preventing and Treating Common Infectious Diseases in Children: A Systematic Review - Jeadran Malagon Rojas; Anastasia Mantziari; Seppo Salminen; Hania Szajewska (MDPI AG, 2022)
Postbiotics have recently been tentatively defined as bioactive compounds produced during a fermentation process (including microbial cells, cell constituents and metabolites) that supports health and/or wellbeing. Postbiotics are currently available in some infant formulas and fermented foods. We systematically reviewed evidence on postbiotics for preventing and treating common infectious diseases among children younger than 5 years. The PubMed, Embase, SpringerLink, and ScienceDirect databases were searched up to March 2019 for randomized controlled trials (RCTs) comparing postbiotics with placebo or no intervention. Seven RCTs involving 1740 children met the inclusion criteria. For therapeutic trials, supplementation with heat-killed Lactobacillus acidophilus LB reduced the duration of diarrhea (4 RCTs, n = 224, mean difference, MD, −20.31 h, 95% CI −27.06 to −13.57). For preventive trials, the pooled results from two RCTs (n = 537) showed that heat-inactivated L. paracasei CBA L74 versus placebo reduced the risk of diarrhea (relative risk, RR, 0.51, 95% CI 0.37-0.71), pharyngitis (RR 0.31, 95% CI 0.12-0.83) and laryngitis (RR 0.44, 95% CI 0.29-0.67). There is limited evidence to recommend the use of specific postbiotics for treating pediatric diarrhea and preventing common infectious diseases among children. Further studies are necessary to determine the effects of different postbiotics.